2023
DOI: 10.1002/alz.13048
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns and dementia‐related neuroimaging markers

Abstract: BACKGROUNDThe exploration of associations between dietary patterns and dementia‐related neuroimaging markers can provide insights on food combinations that may impact brain integrity.METHODSData were derived from the Swedish Gothenburg H70 Birth Cohort Study (n = 610). Three dietary patterns were obtained using principal component analysis. Magnetic resonance imaging markers included cortical thickness, an Alzheimer's disease (AD) signature score, small vessel disease, and white matter microstructural integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The beneficial effects of the MeDi in preventing brain atrophy have been demonstrated [ 4 ], and cross-sectional studies have shown that, among older adults, adherence to the MeDi is associated with larger brain volume [ 5 ], greater cortical thickness [ 6 , 7 ], and better white matter (WM) microstructural integrity [ 8 ]. A longitudinal cohort study conducted in older Scottish individuals showed that lower adherence to the MeDi predicted total brain atrophy during a 3-year period [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of the MeDi in preventing brain atrophy have been demonstrated [ 4 ], and cross-sectional studies have shown that, among older adults, adherence to the MeDi is associated with larger brain volume [ 5 ], greater cortical thickness [ 6 , 7 ], and better white matter (WM) microstructural integrity [ 8 ]. A longitudinal cohort study conducted in older Scottish individuals showed that lower adherence to the MeDi predicted total brain atrophy during a 3-year period [ 9 ].…”
Section: Introductionmentioning
confidence: 99%